2000
DOI: 10.4102/hsag.v5i3.37
|View full text |Cite
|
Sign up to set email alerts
|

The competencies of newly qualified psychiatric nurses

Abstract: This research report comprises part of a larger study, which endeavoured to identifjl the competencies of newly qrralified nurses (NQNs) as viewed by senior professional nurses (SPNs) OPSOMMING Hierdie verslag handel net oor 'n deel van 'n groter studie wat gepoog het om die bedrewenhede van pas gekwolfiseerde verpleegk~indiges ("newly q~ialified nurses -NQNs") te identi@seer soos waargeneem deur senior professionele verpleegk~lndiges ("senio rprofessional nurses -SPNs"). Die verslag jok~is net op die bedrew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This is especially true for the clinical patient care domain competencies which were rated the highest in terms of perceived competence, with more than 50.0% of respondents rating almost all clinical competencies as proficient. Clinical competency demands the acquisition of higher level behaviours in the cognitive, affective and psychomotor domains of learning and these competencies are required to achieve the delivery of high-quality nursing care (Khoza & Ehlers 2000 ). The findings of this study are also supported by other studies that found that community service nurses reported being confident in carrying out patient care activities (Govender et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for the clinical patient care domain competencies which were rated the highest in terms of perceived competence, with more than 50.0% of respondents rating almost all clinical competencies as proficient. Clinical competency demands the acquisition of higher level behaviours in the cognitive, affective and psychomotor domains of learning and these competencies are required to achieve the delivery of high-quality nursing care (Khoza & Ehlers 2000 ). The findings of this study are also supported by other studies that found that community service nurses reported being confident in carrying out patient care activities (Govender et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%